Bourdieu and Media Theory: Explaining Media’s Changes and Continuities in The Post Authoritarian Countries - Wijayanto, Wijayanto (Political Science Program, Universitas Negeri Semarang, 2019)
What happens to the media after the regime changes from authoritarian to the democratic system? Would the media also change accordingly and automatically become free after the regime’s change? Furthermore, what are the forces within and outside the media that influence these changes? This paper aims to review the exiting literatures in the post authoritarian Latin America and Southeast Asia to answer the questions. As a method, this study conducts a critical literature review. This study found that there is agreement among scholars that regime’s change didn’t automatically lead to more free reporting. However, debate is going on about what factors influence the degree of change or continuity with regard to media freedom in post-authoritarian settings. In this regard, scholars have been divided to a theoretical dichotomy. In one hand, there are groups of scholars who believe that political economy factors are the main factors that influence degrees of media freedom. In another hand, there are scholars who believe that cultural factors are more influential. Borrowing the theory of Pierre Bourdie, French sociologists who also concern about this issue, the paper argues that his theory on media’ change can be used as a theoretical framework to examine the media’s changes and overcome the existing theoretical dichotomies.